Applied Linguistics in academic research for postgraduate students in Algerian universities (Journal of Human Sciences, 2023)
This research paper aims to approach the problem of applied linguistic research at the Algerian University through academic research for post-graduation students (Master's and PhD), based on the analytical descriptive approach through which random samples were collected from academic research titles for post-graduation students from the language departments. Arabic in different Algerian universities over a specific period of time, to get acquainted with the most important linguistic fields and trends of applied linguistic research in Algeria.The research concluded that the percentage of research topics in the field of applied linguistics out of the total academic research for post-graduation in the period between 2007-2021 does not exceed 10% of the total. With the predominance of the educational orientation at a rate of 52% for doctoral theses, and a percentage of 66% for master’s theses.